The Traditional or Reverse Algorithm for Diagnosis of Syphilis: Pros and Cons - Ortiz, Daniel A; Shukla, Mayur R; Loeffelholz, Michael J (Clinical infectious diseases, 2020)
Abstract We reviewed relevant syphilis diagnostic literature to address the question “What diagnostic considerations should be taken into account when screening for syphilis using the traditional or reverse algorithm?” Improved laboratory diagnosis of syphilis is an important element of the effort to reduce syphilis rates. Screening for syphilis is performed using either a nontreponemal or treponemal test (part of the traditional or reverse algorithm, respectively). Both syphilis algorithms are used by laboratories. However, there are limited data on the performance and cost-effectiveness of the algorithms. An expert panel generated “key questions” in the laboratory diagnosis of syphilis. This paper pertains to the key factors that should be considered when deciding whether to screen for syphilis using either the traditional or the reverse algorithm. A systematic literature review was performed, and tables of evidence were created to address this question.